2005
DOI: 10.14742/ajet.1343
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation and use of the Online Learning Environment Survey

Abstract: This article reports the development, validation and use of a survey for assessing students' perceptions of their e-learning environments. The Online Learning Environment Survey (OLES) was administered to 325 students, 131 in Australia and 194 in Hong Kong. The data were analysed to examine 1) the reliability and validity of the survey, 2) differences between the perceptions of a) students' actual and preferred environment, b) students and their teacher and c) male and female students and 3) whether associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 23 publications
2
73
0
3
Order By: Relevance
“…The Online Learning Environment Survey (OLES) (Trinidad, Aldridge & Fraser, 2005) was used to assess the health science students' attitudes toward e-learning. The OLES is a dual format instrument where students are asked to rate the actual learning environment experienced in a unit/ course/ subject/ module, compared with their preferred learning environment, using a 5-point rating scale (almost never, seldom, sometimes, often, almost always) for 'actual' and 'preferred' items.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Online Learning Environment Survey (OLES) (Trinidad, Aldridge & Fraser, 2005) was used to assess the health science students' attitudes toward e-learning. The OLES is a dual format instrument where students are asked to rate the actual learning environment experienced in a unit/ course/ subject/ module, compared with their preferred learning environment, using a 5-point rating scale (almost never, seldom, sometimes, often, almost always) for 'actual' and 'preferred' items.…”
Section: Instrumentationmentioning
confidence: 99%
“…The OLES is a dual format instrument where students are asked to rate the actual learning environment experienced in a unit/ course/ subject/ module, compared with their preferred learning environment, using a 5-point rating scale (almost never, seldom, sometimes, often, almost always) for 'actual' and 'preferred' items. The purpose of the OLES is to provide educators using e-learning with a mechanism to reflect on the learning environment provided based on the results gained from student feedback (Trinidad, Aldridge & Fraser, 2005). The OLES incorporates scales from five existing instruments: (1) the What Is Happening In this Class?…”
Section: Instrumentationmentioning
confidence: 99%
“…In a study by Trinidad et al only the category of reliable learning was indicated in this component (27); in a study by Walker and Fraser, however, indices of interaction and cooperation of students as well as learning and learning activities were also included (24). Preparing contents, doing learning activities, and giving feedback timely and properly are among teachers' duties (16).…”
Section: Discussionmentioning
confidence: 99%
“…In studies by Trinidad et al (27) and Walker et al (24), personal compliance and adaptability were introduced as a subclass for self-efficacy. Educational self-efficacy is the ability of people to believe in themselves in order to manage their own learning affairs (30).…”
Section: Teaching Skillsmentioning
confidence: 99%
“…From the items nine scales are derived, which are outlined in Table 1. Internal consistency has been reported by Trinidad, Aldridge, and Fraser (2004) as ranging from 0.86 to 0.96. Content validity and face validity were established through a detailed literature review and input from content knowledge experts.…”
Section: Instrumentationmentioning
confidence: 99%